Phase transformation in Fe–Ti–O composites as potential lead-free piezoelectric materials for energy sensor applications - Aulya Rizqi; Agus Yulianto; Budi Astuti (Universitas Sebelas Maret, 2026)
The Fe₂O₃–TiO₂ composite sintered at 900 °C exhibits a phase transformation from Fe₃O₄ to Fe₂O₃, which significantly affects the functional properties of the material. Composition variations (0:100 to 90:10) result in clear differences in densification, porosity, resistivity, and piezoelectric response. An increase in the Fe₂O₃ fraction strengthens densification but decreases piezoelectric voltage due to limited dipole movement. In contrast, the dominance of TiO₂ favors high resistivity while producing a maximum voltage of 0.01 V at a 10:90 composition. These results confirm that the balance of the Fe₂O₃–TiO₂ ratio determines the optimal combination of properties, as well as underscore the potential of this composite as an environmentally friendly lead-free piezoelectric material for sensor and energy device applications.